HUBUNGAN OBESITAS SENTRAL DENGAN PENYAKIT JANTUNG KORONER DI PUSKESMAS KOTA BOGOR - , SYLVIANA ANDINISARI, dr. Budi Yuli Setianto, SpPD-KKV, SpJP(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background : Obesity is one of the problems associated with an increased risk of disease, one of which coronary heart disease. Coronary heart disease is the leading cause of death in both developed and in developing countries. Objective : This study aims to determine the relationship of central obesity with coronary heart disease in Bogor primary health centers Methods : The research method was observational study with cross sectional approach. The population in the study were all visitor centers are inspected aged 18 and over, according to the exclusion and inclusion criteria, totaling 200 people, 71 men and 129 women. The statistical package was used for analyzing the data. Results : The prevalence of central obesity by 65% or 130 people, 30 men with central obesity (42.3%) and 100 women with central obesity (77.5%). The prevalence of CHD patients as many as 36 people or 18%. CHD patients who have central obesity as many as 24 people (12%). The study on bivariate analysis with chi-square was found that central obesity is not a risk factor for coronary heart disease (RP 1.077, 95% CI 0.574 to 2.020, p 0.817) and this was not statistically significant. Independent variables are statistically significant are the variables of age (RP 2.097, 95% CI 1.127 to 3.900, p 0.025), older age (â¥ 60 years) 2 times higher risk for CHD compared with age 18-59 years. Hypertension increases the risk of CHD 2.4 times (RP 2.381, 95% CI 1.099 to 5.161) than nonhypertensive patients. The results of multivariate analysis with logistic regression showed that none of the independent variables have significant relationships with CHD Stats. Age after consideration of central obesity and hypertension increase the risk of 2 times (RP 2.095, 95% CI 0.861 to 5.094, p 0.103) but not statistically significant. 2.4 times the risk of hypertension to be a CHD after taking into consideration the age and central obesity (RP 2.402, 95% CI 0.970 to 5.946, p 0.058), but not statistically significant. Central obesity as an important substance in this study is included in the multivariate calculations, the results remained not significant relationship with CHD exists Stats after considering age and hypertension (RP 1.102, 95% CI 0.505 to 2.408,p 0,808). Conclusions : There is no relationship between central obesity with incident CHD.